Numerical calibration and experimental validation of a PCM-Air heat exchanger model. (5th March 2017) - Stathopoulos, N.; El Mankibi, M.; Santamouris, Mattheos
Highlights: Development of a PCM-Air heat exchanger experimental unit and its numerical model. Differential Scanning Calorimetry for PCM properties. Ineptitude of DSC obtained heat capacity curves. Creation of adequate heat capacity curves depending on heat transfer rates. Confrontation of numerical and experimental results and validation of the model. Abstract: Ambitious goals have been set at international, European and French level for energy consumption and greenhouse gas emissions decrease of the building sector. Achieving them requires renewable energy integration, a technology that presents however an important drawback: intermittent energy production. In response, thermal energy storage (TES) technology applications have been developed in order to correlate energy production and consumption of the building. Phase Change Materials (PCMs) have been widely used in TES applications as they offer a high storage density and adequate phase change temperature range. It is important to accurately know the thermophysical properties of the PCM, both for experimental (system design) and numerical (correct prediction) purposes. In this paper, the fabrication of a PCM – Air experimental prototype is presented at first, along with the development of a numerical model simulating the downstream temperature evolution of the heat exchanger. Particular focus is given to the calibration method and the validation of the model using experimental characterization results. Differential scanning calorimetry (DSC) is used to define the thermal properties of the PCM. Initial numerical results are underestimated compared to experimental ones. Various factors were investigated, pointing to the ineptitude of the heat capacity parameter, as DSC results depend on heating/cooling rates. Adequate heat capacity curves were empirically determined, depending on heat transfer rates and based on DSC results and experimental observations. The results of the proposed model are confronted with experimental characterization data at different points of the unit and for various airflow rates. A good agreement is observed, showing an average difference ranging from 0.53 °C to 0.75 °C for the surface and PCM values and from 0.87 °C to 1.2 °C for the outlet air temperature values.